PENGGUNAAN Echinodorus radicans DAN Pistia stratiotes UNTUK FITOREMEDIASI AIR TERCEMAR TIMBAL (Pb) SERTA PENGARUHNYA TERHADAP TANAMAN Amaranthus tricolor - Prasidya Perwitasari; Eko Handayanto; Ridesti Rindyastuti (Jurnal Tanah dan Sumberdaya Lahan, 2018)
The existence of industries can cause severe environmental pollution. The impact of environmental pollution can be reduced by phytoremediation by using aquatic plants such as Echinodorus radicans and Pistia stratiotes. This study was aimed to determine the potential of aquatic plants Echinodorus radicans and Pistia stratiotes as lead (Pb) remediators. This study used a completely randomized design with six treatments, i.e. T0F1 (without plant/control 2 ppm), T0F2 (without plant/control 4 ppm), T1F1 (Echinodorus radicans 2 ppm), T1F2 (Echinodorus radicans 4 ppm), T2F1 (Pistia stratiotes 2 ppm), and T2F2 (Pistia stratiotes 4 ppm). The result of this research indicated that T2F2 (Pistia stratiotes 4 ppm) treatment reduced Pb by 92,53% which was higher than T1F2 (Echinodorus radicans 4 ppm) treatment of 89,59%. Pistia stratiotes more effectively reduced Pb content than Echinodorus radicans. Pb contaminated water that was previously used for growing Echinodorus radicans and Pistia stratiotes could be safely used for watering spinach plant (Amaranthus tricolor) to improve its growth